Demographics, Socio-Economic Characteristics, and Risk Factor Prevalence in Patients with Non-Cardioembolic Ischaemic Stroke in Low- and Middle-Income Countries: The OPTIC Registry - Halim Abboud; Julien Labreuche; Antonio Arauz; Alan Bryer; Pablo G Lavados; Ayrton Massaro; Mario Munoz Collazos; Philippe Gabriel Steg; Bassem I Yamout; Eric Vicaut; Pierre Amarenco (My University, 2012)
Background There is a paucity of data on patients with stroke/transient ischaemic attack in low- and middle-income countries. We sought to describe the characteristics and management of patients with an ischaemic stroke and recent transient ischaemic attack or minor ischaemic strokes in low- or middle-income countries. Methods The Outcomes in Patients with TIA and Cerebrovascular disease registry is an international, prospective study. Patients ≥45 years who required secondary prevention of stroke (either following an acute transient ischaemic attack or minor ischaemic strokes (National Institutes of Health Stroke Scale <4) of <24 h duration, or recent (<6 months), stable, first-ever, non-disabling ischaemic stroke) were enrolled in 17 countries in Latin America, the Middle East, and Africa. The main measures of interest were risk factors, comorbidities, and socio-economic variables. Results Between January 2007 and December 2008, 3635 patients were enrolled in Latin America ( n =1543), the Middle East ( n =1041), North Africa ( n = 834), and South Africa ( n = 217). Of these, 63% had a stable, first-ever ischaemic stroke (median delay from symptom onset to inclusion, 25 days interquartile range, 7–77); 37% had an acute transient ischaemic attack or minor ischaemic stroke (median delay, two-days; interquartile range, 0–6). Prevalence of diabetes was 46% in the Middle East, 29% in Latin America, 35% in South Africa, and 38% in North Africa; 72% had abdominal obesity (range, 65–78%; adjusted P < 0·001); prevalence of metabolic syndrome was 78% (range, 72–84%, P < 0·001). Abnormal ankle brachial index (<0·9) was present in 22%, peripheral artery disease in 7·6%, and coronary artery disease in 13%. Overall, 24% of patients had no health insurance and 27% had a low educational level. Interpretation In this study, patients in low- and middle-income countries had a high burden of modifiable risk factors. High rates of low educational level and lack of health insurance in certain regions are potential obstacles to risk factor control. Funding The Outcomes in Patients with TIA and Cerebrovascular disease registry is supported by Sanofi-Aventis, Paris, France.
Keywords: developing countries; epidemiology; prevention; risk factors; socio-economic factors; stroke